Beyond the freedom to refuse patient: A retrospective comparative study of emergency transportation during the COVID-19 pandemic in Japan - Kaiho Hirata; Takuyo Chiba; Reo Takaku; Chen Meilai; Shunya Ikeda; Takashi Shiga (PLoS ONE, 2026)
Emergency department overcrowding and ambulance diversion are significant problems worldwide and have become more apparent during the COVID-19 pandemic. In Japan, the Dedicated Emergency Physician (DEP) model has been associated with reduced transport time. However, whether this benefit persists during the pandemic remains unclear. This study analyzed the changes in transport outcomes during the COVID-19 pandemic in Japanese regions with and without DEP hospitals to evaluate the effectiveness of the DEP model and identify factors that could improve transport outcomes. Using nationwide data from January 2015 to December 2021, three target areas were analyzed: Urayasu-Ichikawa (DEP Group 1), Shonan-Fujisawa (DEP Group 2), and Ichinomiya-Toyota (Non-DEP Group 3). DEP Groups 1 and 2 contained DEP hospitals, while Non-DEP Group 3 was selected for its comparable population size and strong pre-pandemic transport performance. To minimize the impact of regional variations in COVID-19 prevalence, this study compared the changes in transportation outcomes before and after the pandemic between the target areas and nearby comparison areas. In total, there were 150,856 transports in Group 1; 186,965 in Group 2; and 516,655 in Group 3. In the target areas of Groups 2 and 3, transport time changes were significantly shorter by 2.016 and 0.606 min, respectively, compared to the comparison areas. Moreover, these areas had significantly lower odds of transportation difficulty (Group 2: odds ratio 0.131, 95% confidence interval 0.110–0.157; Group 3: OR 0.086, 95% CI 0.066–0.112). It was found that the common characteristics of these areas were densely located large-scale hospitals and makeshift buildings for patients with COVID-19, adjacent to large-scale hospitals. These findings suggest that DEP hospitals alone did not guarantee favorable transport outcomes during the pandemic. A sufficient number of large-scale hospitals and nearby temporary facilities may be crucial for maintaining effective emergency transportation during a pandemic.